The Impact of Environmental Turbulence on Product Innovation in Small to Medium Enterprises in Harare, Zimbabwe - Zimuto, Caroline; Sandada, Maxwell; Chuchu, Tinashe; Ndoro, Tinashe (Journal of Economics and Behavioral Studies, 2019)
The purpose of the research was to examine the impact of environmental turbulence on product innovations in small to medium enterprises (SMEs). In the study environmental turbulence consisted of five dimensions namely, supplier turbulence, technological turbulence, market turbulence, regulatory turbulence and competitive intensity. A cross-sectional quantitative research design was adopted in the study. The study sample was drawn from a pool of 3,000 SMEs both unregistered and registered with the Ministry of Small and Medium Enterprises in Harare, Zimbabwe. In the study, a total of 200 completed surveys were obtained and analysed. To analyse the research data SPSS23 was utilised. Regression analysis was carried out to establish the cause-and-effect relationship between the independent and dependent variables in the study. The findings of the study showed that technology turbulence and competitive intensity had a statistically significant positive impact on product innovation. Market turbulence was noted as having a statistically significant negative impact on product innovativeness. The main implications established in the study were that SMEs should introduce mechanisms to manage and mitigate market, supplier and regulatory turbulence to ensure that their levels of product innovativeness remain positive.